PENGARUH PROGRAM PARENTING TERHADAP PERKEMBANGAN KEMANDIRIAN ANAK USIA DINI (STUDI PADA PAUD PARAMATA BUNDA KOTA PALOPO) - Syamsu S. (Palita: Journal of Social Religion Research, 2017)
This study aims to determine the effect of parenting program on the development of early child self-reliance at PAUD Paramata Bunda Palopo. The type of this research is descriptive quantitative expost facto model, which result is described in the form of percentage or number. The study population amounted to 172 people (160 parent learners, 12 teachers) parent sample of students taken 20% = 32 people (variable X). While the population as well as the sample of teachers as many as 12 people (variable Y). Data collection techniques are questionnaires, interviews, and documentation. Further analysis of quantitative descriptive data in the form of percentage technique and mean score. The results showed that the implementation of parenting programs positively influences the development of child self-reliance in PAUD Paramata Mother of Palopo City. The implication of this research is that every parent has moral obligation to participate in the implementation of educational programs so that synchronization between parent and school side toward early child development stage.